CASH TRANSFERS AND CAREGIVERS: WORKING TOGETHER TO REDUCE VULNERABILITY AND HIV RISK AMONG ADOLESCENT GIRLS IN JOHANNESBURG, SOUTH AFRICA - Hill, Naomi; Hochfeld, Tessa; Patel, Leila (Social Work/Maatskaplike Werk, 2021)
In South Africa adolescent girls have the highest HIV incidence of any sex or age cohort. Scalable HIV-prevention interventions targeting this group are critical for epidemic control. Reaching 12.2 million children, the Child Support Grant mitigates the socio-structural drivers of HIV risk. This qualitative study of eight adolescents and their caregivers in Westbury, Johannesburg, explored how caregiving increases protective potential. ‘Caregiving’ enhanced the HIV risk-reduction benefits of ‘cash’ when characterised by substantial positive caregiver-adolescent involvement and adequate levels of control and consistency. Results underpin the value of social protection as an HIV-prevention modality and endorse investment in caregiver support programmes.